Pengaruh Daya Tarik dan Keuatan Iklan Terhadap Minat Beli Di Kota Makassar - Ratna Dewi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
Objectively, this study aims to examine and examine the effect of advertising attractiveness and advertising power simultaneously on buying interest in Makassar City. This study involved a sample of 75 as many as respondents using Mobile Advertising in Makassar City. This study uses primary data collected using a questionnaire. Methods of descriptive data analysis and multiple regression analysis models partially or simultaneously test the relationship between the independent and dependent variables. The results showed that partially the advertising attractiveness variable had a significant influence on buying interest in the city of Makassar. The power of advertising can make a positive contribution to consumer buying interest in Makassar. Submission of information through messages that are easy to remember, different from competitors create a need to increase consumer buying interest. Simultaneously the attractiveness of advertising and the power of advertising has a positive and significant effect on consumer buying interest in Makassar City